2022
DOI: 10.3389/fnagi.2022.830494
|View full text |Cite
|
Sign up to set email alerts
|

Is Immune Suppression Involved in the Ischemic Stroke? A Study Based on Computational Biology

Abstract: ObjectiveTo identify the genetic mechanisms of immunosuppression-related genes implicated in ischemic stroke.BackgroundA better understanding of immune-related genes (IGs) involved in the pathophysiology of ischemic stroke may help identify drug targets beneficial for immunomodulatory approaches and reducing stroke-induced immunosuppression complications.MethodsTwo datasets related to ischemic stroke were downloaded from the GEO database. Immunosuppression-associated genes were obtained from three databases (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
0
14
0
3
Order By: Relevance
“…It has become the primary cause of disability among adults in China [ 2 , 3 ]. According to the investigation report [ 4 6 ], stroke has the highest incidence, mortality, and disability among all nervous system diseases, and it is the second largest risk factor for death in people over 60 years old. Stroke is the third largest factor affecting human lifespan as a worldwide medical problem.…”
Section: Introductionmentioning
confidence: 99%
“…It has become the primary cause of disability among adults in China [ 2 , 3 ]. According to the investigation report [ 4 6 ], stroke has the highest incidence, mortality, and disability among all nervous system diseases, and it is the second largest risk factor for death in people over 60 years old. Stroke is the third largest factor affecting human lifespan as a worldwide medical problem.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the principle of “guilt by association” ( Oliver, 2000 ), whose central idea is that functional similar genes and their products often have either physical interactions or functional associations, which plays a prominent role in the development of computer algorithms for predicting novel relative genes based on known disease genes ( Wu et al, 2008 ; Luo et al, 2019 ; Liang et al, 2021 ; Zhang et al, 2021 ; Wang et al, 2022 ). The STRING database ( Keshava et al, 2009 ) is a reliable database that contains large amounts of molecular protein-protein interaction (PPI) data obtained from various sources.…”
Section: Introductionmentioning
confidence: 99%
“…Using a rat model of cerebral ischemia, Wang et al reported that the Jak2 inhibitor AG490 could improve neurological deficits, cerebral infarction, edema, oxidative stress, and inflammation ( Wang et al, 2021 ). A recent study also identified Jak2 as an immune-related gene involved in IS pathophysiology ( Wang et al, 2022 ). However, the roles of DPF2 , LMNB1 , and MLLT3 in IS remain to be explored.…”
Section: Discussionmentioning
confidence: 99%